Bibliometric Analysis of the Term Toxic Positivity in Workplace - Felicia, Felicia (Westscience Press, 2025)
Toxic positivity in the Workplace refers to the excessive promotion of optimism while discouraging the expression of negative emotions, which can lead to psychological distress, burnout, and decreased employee well-being. This study employs bibliometric analysis to examine research trends and key themes related to toxic positivity in professional settings, identifying four major clusters: psychological impact, workplace stress, organizational culture, and the role of positive psychology. Findings indicate that toxic positivity can suppress emotional authenticity, increase stress, and create unrealistic Performance expectations, ultimately affecting job satisfaction and organizational dynamics. The study underscores the need for interdisciplinary collaboration in addressing this phenomenon, highlighting the importance of fostering psychological safety and emotional balance in the Workplace to support employee wellbeing and a more inclusive organizational culture.